REPRODUKSI KEKUASAAN DAN KONVERSI MODAL DI TEMPAT KERJA: DAMPAK TRANSISI PERFORMANCE-BASED PAY DI JEPANG - Frichicilia Grace Stahlumb; Ivandra Solihin; Teddy Chrisprimanata Putra (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The transition of the wage system in Japan from seniority-based pay to performance-based pay following the Japanese Economic Bubble is conventionally framed within the discourse of managerial efficiency and economic recovery. However, this research aims to critically deconstruct this phenomenon as a mechanism of power reproduction and institutional discipline within the corporate arena. By employing a Systematic Literature Review (SLR) methodology integrated with a political sociology perspective, this study conducts a structural-thematic analysis of policy documents and labor survey reports. The findings reveal that the dismantling of traditional employment pillars functions as an instrument for the capitalist class to transfer the risks of economic volatility directly onto the working class. This transition forcibly disrupts the workers' cultural habitus, compelling them to execute a radical capital conversion from social capital (institutional loyalty) to short-term productivity capital to preserve their economic bargaining power. Furthermore, managerial hegemony, manifested through ambiguous evaluation criteria and high appraiser subjectivity, evidences a profound power asymmetry that erodes trust and communal cohesion in the workplace. This study concludes that the legitimacy of performance-based pay cannot rely solely on hegemonic imposition; instead, it demands class compromise and negotiation. Corporations must facilitate transparency and avenues for workers' self-actualization to transfigure exploitative practices into an equitable consensus.